2019
DOI: 10.1186/s13104-019-4713-2
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey on sleep quality, mental health, and academic performance among medical students in Saudi Arabia

Abstract: Objective Adequate sleep is integral to better mental health and facilitates students’ learning. We aimed to assess sleep quality among medical students and to see whether it was associated with their mental health (e.g., depression, anxiety, and stress) and academic performance. Results A total of 206 responded, and 95 of them had complete data on demography, lifestyle, academic performance, sleep quality (Pittsburgh Sleep Quality I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
117
5
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(167 citation statements)
references
References 18 publications
(22 reference statements)
21
117
5
24
Order By: Relevance
“…Medical students are especially prone to poor sleep quality because of the physically and emotionally challenging and intense training they undertake ( Wong et al, 2005 ). Poor sleep affects neurocognitive and psychomotor performance, emotional wellbeing, working capacity, academic performance, physical and mental health as well as quality of life ( Al-Khani et al, 2019 ; Flores, 2009 ; Giri, Baviskar & Phalke, 2013 ; Mume, Olawale & Osundina, 2011 ). Due to lockdown measures and travel restrictions, students are facing decreased physical activity, lack of schedule, altered living conditions, increased screen time and time spent in social media, and altered sleep wake schedule including increased daytime nap duration ( Majumdar, Biswas & Sahu, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Medical students are especially prone to poor sleep quality because of the physically and emotionally challenging and intense training they undertake ( Wong et al, 2005 ). Poor sleep affects neurocognitive and psychomotor performance, emotional wellbeing, working capacity, academic performance, physical and mental health as well as quality of life ( Al-Khani et al, 2019 ; Flores, 2009 ; Giri, Baviskar & Phalke, 2013 ; Mume, Olawale & Osundina, 2011 ). Due to lockdown measures and travel restrictions, students are facing decreased physical activity, lack of schedule, altered living conditions, increased screen time and time spent in social media, and altered sleep wake schedule including increased daytime nap duration ( Majumdar, Biswas & Sahu, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown a very high prevalence of poor sleep quality, daytime sleepiness, and insomnia. [11][12][13][14][15] A study conducted among 2,095 adults in Riyadh showed that one in every three Saudi adults is suffering from short sleep duration of less than 7 hours per night. 16 Another study strongly related short sleep duration among Saudi adolescents to an increased risk of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Medical students are especially prone to poor sleep quality because of the physically and emotionally challenging and intense training they undertake (Wong et al 2005). Poor sleep affects neurocognitive and psychomotor performance, emotional wellbeing, working capacity, academic performance, physical and mental health as well as quality of life (Al-Khani et al 2019;Flores 2009;Giri et al 2013;Mume et al 2011). Due to lockdown measures and travel restrictions, students are facing decreased physical activity, lack of schedule, altered living conditions, increased screen time and time spent in social media, and altered sleep wake schedule including increased daytime nap duration (Majumdar et al 2020).…”
Section: Discussionmentioning
confidence: 99%